Conditions, Needs and Guidelines for Self and Professional Development of Teachers in Schools Under the Nakhon Phanom Primary Educational Service Area Office 1 - Chaipakdee, Banjamas; Sornphet, Supakorn; Hanrin, Chanwit (Journal of Education Rajabhat Maha Sarakham University, 2022)
The purposes of this research were: (1) to study the current and desirable conditions, (2) to assess the needs and (3) to develop guidelines for self and professional development of teachers in schools under the Nakhon Phanom Primary Educational Service Area Office 1. The research sample group totally 270 persons. The sample size was specified by percent criterion and Stratified Random Sampling. The research instruments: (1) the current condition questionnaire, (2) the desirable condition questionnaire, (3) the structured interview form, and (4) the assessment form of suitability and possibility assessment. The statistical data analysis were percentage, mean, standard deviation and Modified Priority Needs Index (PNImodified). The results of the research showed that: (1) the overall current condition was at a high level and the overall desirable conditions was at the highest level. (2) The results of PNImodified for self-development and profession of teachers in schools ranked were as follows: 1) development of innovation in learning management, 2) participation and leadership in exchanging professional knowledge, and 3) systematic and continuous self-development. (3) The guidelines for self-development and profession consisted of 3 aspects as follows: 1) systematic and continuous self-development, teachers attempted and sought opportunities for self-improvement in the form of education. 2) participation and leadership in exchanging professional knowledge. 3) development of innovation in learning management. The results of development guideline assessment revealed the suitability and the possibility in overall at the highest level.